KAJIAN SPEKTROSKOPI FTIR, XRD DAN SEM KAOLIN ALAM ASAL TATAKAN, KALIMANTAN SELATAN HASIL PURIFIKASI DENGAN METODE SEDIMENTASI - sunardi sunardi (Program Studi Kimia, Universitas Lambung Mangkurat, 2010)
This study aimed at demonstrating complementary roles offered by Fourier transform infrared spectrophotometry, X-ray powder diffraction (XRD) and Scanning Electron Microscope (SEM) techniques in characterizing clay fraction of kaolins. The clay fraction of kaolin samples from Tatakan, South Kalimantan, Indonesia was purificated by sedimentation methods and siphoning to obtain pure kaolinite and to reduce the quartz mineral and the others impurities. Main peaks in the infrared spectra reflected Al-OH, Al-O and Si-O functional groups in the high frequency stretching and low frequency bending modes and were those for kaolinite but possible absorption interferences peaks for quartz and the other impurities are inferred. The XRD results identified kaolinite as the major minerals phase with confirmed presence of quartz, chlorite, halloysite and christobalite as minor quantities in the samples. Furthermore, the purification process increased the composition of kaolinite, specific surface area , total pore volume and cation exchange capacity of kaolin were about 30-35%. Keyword: natural kaolin, purification, sedimentation, siphoning